2019
DOI: 10.1108/jmp-07-2018-0318
|View full text |Cite
|
Sign up to set email alerts
|

Managers’ regulatory focus, temporal focus and exploration–exploitation activities

Abstract: Purpose The purpose of this paper is to examine and gain further insight into the potential link between regulatory focus and exploration–exploitation at the individual manager level. More specifically, the authors hypothesised that temporal focus would act as a mediator in the relationship between managers’ regulatory foci and exploration–exploitation activities. Design/methodology/approach A survey was conducted with 541 managers from the USA. The model was tested using OLS regression models, followed by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 54 publications
(112 reference statements)
0
22
0
Order By: Relevance
“…Temporal foci are defined as ‘allocation of attention to the past, present, and future’ (Shipp et al, 2009: 2); a future focus is associated with envisioning what the future is likely to bring. Concurrently, exploration has been conceptualised as a long-term activity with unclear outcomes in the distant future (Mom et al, 2009; Tuncdogan and Dogan, 2019). Exploration involves the development of new market possibilities, strong renewal or even the acquisition of new skills – all activities that have a long-term future focus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporal foci are defined as ‘allocation of attention to the past, present, and future’ (Shipp et al, 2009: 2); a future focus is associated with envisioning what the future is likely to bring. Concurrently, exploration has been conceptualised as a long-term activity with unclear outcomes in the distant future (Mom et al, 2009; Tuncdogan and Dogan, 2019). Exploration involves the development of new market possibilities, strong renewal or even the acquisition of new skills – all activities that have a long-term future focus.…”
Section: Methodsmentioning
confidence: 99%
“…Concurrently, exploration has been conceptualised as a long-term activity with unclear outcomes in the distant future (e.g. Mom et al, 2009;Tuncdogan and Dogan, 2019). Exploration involves the development of new market possibilities, strong renewal, or even the acquisition of new skills -all activities that have a long-term future focus.…”
Section: Validity Of Coding Exploration and Exploitationmentioning
confidence: 99%
“…Previous research has identified regulatory focusa motivational theory of goal attainment as a key CEO-related condition, or microfoundation, of organizational ambidexterity (Lanaj et al, 2012;Gorman et al, 2012;Kammerlander et al, 2015;Tuncdogan et al, 2017;Tuncdogan and Dogan, 2019). It is "a known antecedent of several concepts that correspond to the concepts by which exploration and exploitation are defined" (Tuncdogan et al, 2015, p. 14).…”
Section: Regulatory Focus and Ambidexteritymentioning
confidence: 99%
“…Over the last decade, international research has produced a large number of studies that have shown the importance of temporal focus in various aspects of the lives of individuals, groups and organizations [ 3 5 ]. Some researchers have, for example, investigated temporal aspects related to attitudes [ 6 8 ], motivations [ 9 – 11 ], individual behaviours [ 12 14 ], the effects of time on team processes and performance [ 15 , 16 ], the role of time in organizational and strategic decisions [ 17 19 ] and the dimensions of socio-cultural influence that shape the shared representations of time [ 20 ].…”
Section: Introductionmentioning
confidence: 99%